DISHARMONI PENGATURAN TINDAK PIDANA POLITIK UANG DALAM UNDANG-UNDANG PEMILU DAN UNDANG-UNDANG PILKADA - Aditya Wiguna Sanjaya (Jurnal Magister Hukum Perspektif, 2025)
The regulatory dichotomy between regional elections and general elections for the president, vice president, members of the DPR, DPRD and DPD (elections) has led to differences in arrangements between the two, one of which is regarding regulation of money politics, which in this case is interpreted as an attempt to give or promise something to voters to not exercise their right to vote or vote for a particular candidate. Arrangements regarding the prohibition of giving or promising something to voters not to exercise their right to vote or vote for certain candidates in the Pilkada Law are formed in pairs, both for the giver and also for the recipient, namely as stipulated in Article 187 A paragraph (1) and paragraph (2) of the Pilkada Law, while for the same material actions the Election Law only contains a prohibition for the giving party, as stipulated in Article 523 of the Election Law, while for the receiving party there are no prohibitions or criminal sanctions in the a quo law. This shows that there is disharmony between the Pilkada Law and the Election Law, especially in the Election Law it appears that there is a legal vacuum (vacuum of norm) regarding the prohibition for receiving parties in the practice of money politics. This research departs from two problems. First, is the regulation of money politics as a crime in the Election Law reflecting justice. Second, what is the ideal policy for formulating money politics in the context of ius constituendum? The research method used in writing this paper is normative research method. The results of the study show that the regulation of money politics as a crime in the Election Law does not yet reflect justice, for this reason it is necessary to reconstruct the regulation of money politics in the future Election Law, namely by criminalizing passive money politics. Keywords: Disharmony, Crime, Money Politics, Elections